Lixiviación en tanques abiertos de los arseniuros de una fundición de plomo en la Sierra Central, Perú - Rivera Del Valle, Luis Américo (2022)
The arsenic content of a smelter's gaseous emissions represents a serious risk to human health, as they are reported in soils and waters. Within a smelter's operations, by-products with high arsenic content recirculate indefinitely instead of being drained. In order to provide an environmental alternative, the present research work evaluates the Acid Oxidative Leaching process that uses the H2SO4 - H2O2 mixture to dissolve the arsenides, which must be completed with environmental removal by precipitation as Scorodite; a process known and accepted worldwide. The optimal parameters obtained are: 240 kg/t of H2O2, concentration of 120 g/L of H2SO4, L/S ratio of 9/1 and as iron contributor: 170 kg/t of copper tailings, with which solutions of 56% As and 90% Cu; item whose recovery pays for the process.